1987
DOI: 10.1111/j.1365-2621.1987.tb13978.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification of an Antioxidizing Component in Raw Cow Milk

Abstract: Gel filtration was used to partially purify the antioxidizing component of a centrifuged serum of raw cow milk, and its properties were studied. The antioxidizing effect did not decrease after dialysis or heating. The finding of no change after dialysis suggested that the compound was of high molecular weight, estimated at 38,000 by gel filtration. The antioxidizing effect decreased with irradiation, accompanied by a parallel decrease in the riboflavin content. The antioxidizing component of this serum fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…l), in agreement with earlier results (Toyosaki et al, 1987b). TLC also showed that protein-bound riboflavin inhibited hydroperoxide formation (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…l), in agreement with earlier results (Toyosaki et al, 1987b). TLC also showed that protein-bound riboflavin inhibited hydroperoxide formation (Fig.…”
Section: Resultssupporting
confidence: 91%
“…THE FORMATION of hydroperoxides was inhibited by protein-bound riboflavin in a water system in the dark (Fig. l), in agreement with earlier results (Toyosaki et al, 1987b). TLC also showed that protein-bound riboflavin inhibited hydroperoxide formation (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We previously studied silky fowl eggs from a sitology perspective, examining a variety of phenomena induced during bread fermentation and baking, and reported new findings based on these studies [7][8][9][10][11][12]. Most of the studies focused on fat as the main nutritional ingredient, and the sitological functional properties of silky fowl egg albumen have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%